Fostering Food Sustainability: Enhancing Awareness of Local Food Consumption Among Secondary School Students - Nashar, Nashar; Supriatna, Nana; Komalasari, Kokom (FKIP Universitas Lampung, 2025)
Abstract: Fostering Food Sustainability: Enhancing Awareness Of Local Food Consumption Among Secondary School Students. Background and Objective: This study aims to explore the awareness of secondary school students regarding local food consumption, particularly in Serang City, Indonesia, through indicators of knowledge, attitudes, and behavior. Method: Involving 325 students, the research employed a quantitative approach with a cross-sectional survey design. Findings: The findings revealed that 70.2% of students demonstrated a good understanding of local food sustainability; however, only 61.4% showed positive attitudes, and 54.8% exhibited behavior aligned with local food consumption in daily life. Pearson correlation analysis indicated a significant but weak relationship between students’ knowledge and attitudes (r=0.112; p<0.05), while the relationships between knowledge and behavior, as well as attitudes and behavior, were not statistically significant. These inconsistencies suggest that increasing knowledge does not automatically lead to positive attitude and behavior changes. Therefore, a more integrated approach to food sustainability education is required, including the incorporation of sustainability themes into school curricula, project-based learning, and policies to control the availability of unhealthy processed foods on school campuses. These strategies align with achieving Sustainable Development Goals (SDG) 3 (Good Health and Well-being), SDG 4 (Quality Education), and SDG 12 (Responsible Consumption and Production). Conklusion: In conclusion, while students demonstrate a good theoretical understanding, more effective interventions are needed to encourage the adoption of attitudes and behaviors that support sustainable and healthy local food consumption. This study recommends collaboration among the government, educational institutions, and communities to create a generation more conscious of food sustainability.Keywords: education, food sustainability, local food consumption, SDGs.